A Forensic And Multidisciplinary Inquiry Into Corporate Malfeasance Within The Indian Optical Market: Structural Dynamics, Compliance Evasion, And Ethical Breach Analysis - Mr. Ajay Nagar; Dr. Monika Rastogi (Revista Electronica de Veterinaria, 2024)
A forensic and multidisciplinary inquiry into corporate malfeasance within the Indian optical market uncovers a complex web of structural inefficiencies, regulatory shortcomings, and ethical lapses that collectively enable a range of illicit practices. The study integrates perspectives from forensic accounting, corporate governance, legal analysis, and ethical theory to investigate how businesses within the sector manipulate systemic weaknesses for financial and competitive gain. By analyzing real-world case studies alongside statistical data, the research reveals how the concentration of market power, ambiguous regulatory frameworks, and insufficient oversight create conditions that foster corporate misconduct. Corporate malfeasance in this domain often manifests through various evasion tactics, including falsification of financial statements, misreporting of revenue, manipulation of supply chains, and the deliberate exploitation of loopholes within compliance and reporting mechanisms. These activities are not isolated but represent deeply embedded patterns within certain organizational cultures that prioritize profit over legality and ethical responsibility. Such misconduct not only threatens market fairness but also erodes stakeholder trust, impacting consumers, smaller competitors, regulatory institutions, and the broader economic ecosystem. The inquiry further investigates the ethical breaches committed by corporate actors, examining how compromised internal controls, lack of accountability, and weak ethical leadership contribute to a pervasive culture of non-compliance. Ethical violations are contextualized within a broader organizational and institutional framework, illustrating how systemic failures often reinforce unethical behavior. In response to these challenges, the study calls for a more proactive and coordinated regulatory approach that combines rigorous oversight with capacity-building measures for ethical compliance. Strengthening transparency, reforming audit and reporting standards, and fostering an internal culture of accountability are identified as essential strategies for long-term sectoral reform. Furthermore, the research emphasizes the importance of cross-sector collaboration—bringing together regulators, corporate entities, forensic experts, and consumer advocacy groups—to establish robust mechanisms for early detection and prevention of malpractice. Ultimately, the inquiry advocates for a resilient, transparent, and ethically governed optical market in India. Such a transformation is crucial not only for protecting consumer interests and promoting fair competition but also for ensuring sustainable growth and public trust in one of India’s rapidly expanding healthcare and consumer goods sectors.